The relationship between the prevalence of dental space infections in Pediatric patient and parents’ awareness (Bangladesh Journal of Medical Science, 2023)
Background: The facial spaces in head and neck are the potential spaces between the various layers of fascia normally filled with loose connective tissue and bounded by anatomical barriers, usually of bone, muscle or facial layers.Objective: To evaluate the level of knowledge and awareness about space infection among pediatric patients and their parents in Riyadh, KSA which can lead to seeking early help.Results: A total of 102 children (56 girls, 46 boys; mean age from 2-12 years) visited Dar al Uloom hospital since January 2019. Most of the patients (51 cases) were children aged 6–9 years. It has been observed that majority of 10- 12 years old children noticed pain first (58.3%) followed by abscess drainage (25%) whereas, large number of 2-5 years old children noticed pain as the first option (66.7%) followed by swelling (26.7%). Further, a greater number of 6-9 years old children noticed pain (80.4%) followed by swelling (7.8%). These results suggest that the association of the first symptom observed by the child with different age groups was found to be significant.Conclusion: In our study, the most common age group of pediatric patient infected with space infection was from 6-9 years, and the most common source of infection was caries. The level of education does not affect the awareness. It was observed that the symptoms of space infection were first noticed by the child, and it was due to the lack of early visits to the dentist. Hence, there is a need of increased awareness of the parents towards space infection and its potential risk.Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 773-777